The Implementation of Technology Ethics in Government Accountants-Based E-Government Public Services: Theoretical and Conceptual Review - Emilia Desi Listyaningsih*; Widi Hidayat (Riwayat: Educational Journal of History and Humanities, 2023)
The demands of technological advancements affect all professional fields, one of which is government accounting, which implements e-Government to optimize the effectiveness and efficiency of public services. As the use of e-government continues to rise, the emergence of ethical issues is unavoidable. Various efforts are made as preventive measures, such as improving the e-government service system and network. However, beyond that, the focus of attention should not only be on enhancing the capabilities of human resources as the primary designers of e-Government services to meet the needs of stakeholders but also on developing ethics in technology to anticipate the same technology's impact not harming unrelated parties. This paper conceptually examines and reviews the literature on the crucial role of technology ethics in the implementation of e-Government through transparent and accountable financial reporting to achieve good governance. Thus, the objective of this research is to gain a critical understanding of ethics in implementing technology-based public services. The implications of this paper call for further research on technology ethics, both qualitative and quantitative, to obtain detailed results that are beneficial for the future development of e-government technology, especially for governments as policy makers in public services.